Evaluation of Oxidative Status in Elderly Patients with Multiple Cerebral Infarctions and Multiple Chronic Total Coronary Occlusions. (28th June 2022) - Li, Xia; Guo, Dianxuan; Hu, Youdong; Chen, Ying
Abstract : Background . Oxidative stress plays a key role in atherosclerosis. Acting via high level of reactive oxygen species, an increase of oxidative stress is involved in the pathogenesis and progression of atherosclerostic stenosis or occlusion of arteries. Oxidative stress leads to an accumulation of oxidized low-density lipoprotein, which plays important roles in steno-occlusion of cerebral and coronary arteries. However, the exact reasons for multiple cerebral and coronary artery steno-occlusion in elderly patients remain unclear. The aim was to evaluate the effects of imbalance of oxidative/antioxidative status on concomitant multiple brain infarcts and multiple chronic total coronary occlusions in elderly patients. Methods . We measured the circulating levels of malondialdehyde (MDA), reactive oxygen species (ROS), thiobarbituric acid reactive substance (TBARS), advanced oxidation protein products (AOPP), superoxide dismutase 1 (SOD 1), superoxide dismutase 2 (SOD 2), superoxide dismutase 3 (SOD 3), and paraoxonase 1 (PON 1) in patients with concomitant multiple cerebral infarcts and multiple chronic total coronary occlusions. Results . Circulating levels of oxidative stress markers (MDA, ROS, TBARS, and AOPP) were increased (P < 0.001 ) and antioxidative stress markers (SOD 1, SOD 2, SOD 3, and PON 1) were decreased (P < 0.001 ) in elderly patients with concomitant multiple brain infarcts and multiple chronic total coronary occlusions. Conclusions . The findings suggested that the imbalance of oxidative/antioxidative status may be associated with multiple cerebral infarcts and multiple chronic total coronary occlusions and may contribute to the development of concomitant multiple brain infarcts and multiple chronic total coronary occlusions in elderly patients.